2016
DOI: 10.1016/j.eururo.2016.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Ejaculation Frequency and Risk of Prostate Cancer: Updated Results with an Additional Decade of Follow-up

Abstract: Background Evidence suggests that ejaculation frequency may be inversely related to the risk of prostate cancer (PCa), a disease for which few modifiable risk factors have been identified. Objective To incorporate an additional 10 yr of follow-up into an original analysis and to comprehensively evaluate the association between ejaculation frequency and PCa, accounting for screening, clinically relevant disease subgroups, and the impact of mortality from other causes. Design, setting, and participants A pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 33 publications
3
38
0
15
Order By: Relevance
“…Finally, this systematic review only included 2 studies. 12,13 The studies screened of this process was shown in Figure 1. Characteristics of patient were summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, this systematic review only included 2 studies. 12,13 The studies screened of this process was shown in Figure 1. Characteristics of patient were summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…PCa was less frequently diagnosed among men who had the higher ejaculation frequency (21 or more ejaculations per month, multivariable HR, 95% CI, 0.81, (0.72, 0.92), P<0.0001 for trend, ages 20 to 29 years; multivariable HR, 95% CI, 0.78, (0.69, 0.89), P<0.0001 for trend, ages 40 to 49 years] compared with men reporting 4 to 7 ejaculations per month. 13 The two trials 12,13 indicated that higher ejaculation frequency is associated with reducing risk of PCa. However, lower ejaculation frequency is not associated with reducing risk of PCa.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PDE5i use may lower prostate cancer risk, possibly because men who use them may ejaculate more frequently, which protects against prostate cancer. 128,129 Long-term sildenafil citrate (Viagra) use is associated with a slightly increased risk for melanoma. 130 Most common side effects of PDE5i include headache in up to 20% of men, flushing in up to 15%, and dyspepsia and nasal congestion in up to 10%.…”
Section: Pde5 Inhibitorsmentioning
confidence: 99%